Faithful Citizenship: Exploring the Theological Imperative and Societal Impact of Tax Compliance Among Christians in Indonesia - Prayogo, Thomas Handoyo; Herman, Samuel (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
This journal explores the spiritual responsibility of tax compliance among church members, emphasizing the biblical principles and governmental regulations governing taxation. It delves into the duty of church leaders to educate congregants on tax obligations, aiming to enhance awareness and adherence. The study underscores the significance of understanding taxation principles for improved compliance and suggests that such knowledge positively impacts the church's tax-related actions. Ultimately, it emphasizes the integration of Matthew 5:16, encouraging church members to let their light shine through responsible tax practices.